Decomposition of the Changes in Household Disposable Income Distribution in China - Chen Gong; Denisa Maria Sologon; Zina Nimeh; Cathal O'Donoghue (Institute of Labor Economics (IZA), 2023)
Studies have shown that the previously growing inequality in China has stabilized and even declined since 2008 (Kanbur et al., 2021), nevertheless, the drivers of the latest trans-formation in income inequality remain to be unraveled. We address this research gap by examining the changes in the distribution of household disposable income and its drivers in China from 2010 to 2016. We apply the distributional decomposition method proposed by Bourguignon et al. (2008) and Sologon et al. (2021), and quantify the contribution of all factors into four general dimensions, (1) demographic composition, (2) labor market structure, (3) price and return, and (4) governmental transfers. This study considers not only the individual labor income as with existing literature, but also models other family incomes and social transfers to reflect the real economic conditions more accurately. The decomposition results show that all four factors contribute positively to the decline in income inequality during the period studied. The changes in urban labor market structure, specifically the general forms of employment, occupational and industrial structure, have been contributing as inequality augmenting factors.
Keywords: D63; D31; F63; 330; income distribution; decomposition; income inequality; microsimulation; overtime comparison; labor market structure; demographic structure